Exome sequencing identifies compound heterozygous mutations in C12orf57 in two siblings with severe intellectual disability, hypoplasia of the corpus callosum, chorioretinal coloboma, and intractable seizures. Issue 8 (5th May 2014) - Platzer, Konrad; Hüning, Irina; Obieglo, Carolin; Schwarzmayr, Thomas; Gabriel, Rainer; Strom, Tim M.; Gillessen‐Kaesbach, Gabriele; Kaiser, Frank J.
<x xml:space="preserve">Abstract</x> In patients with genetically heterogeneous disorders such as intellectual disability or epilepsy, exome sequencing is a powerful tool to elucidate the underlying genetic cause. Homozygous and compound heterozygous mutations in C12orf57 have recently been described to cause an autosomal recessive syndromic form of intellectual disability, including agenesis/hypoplasia of the corpus callosum, optic coloboma, and intractable seizures. Here, we report on two siblings from nonconsanguineous parents harboring two compound heterozygous loss‐of‐function mutations in C12orf57 identified by exome sequencing, including a novel nonsense mutation, and review the patients described in the literature. © 2014 Wiley Periodicals, Inc.